Preoperative assessment of pediatric supracondylar humeral fractures by orthopaedic residents and orthopaedic surgeons: is there a difference?. Issue 2 (March 2019) - Haruno, Lee S.; Hill, Jaclyn F.; Sanderson, Cody J.; Browne, Theodora; Zhu, Huirong; McKay, Scott D.
Abstract : Background: The urgency of pediatric supracondylar humeral (SCH) fracture treatment is influenced by preoperative evaluation and neurovascular integrity. This assessment often is completed by a resident. The purpose of this analysis was to determine differences in assessments made by orthopaedic residents and attending physicians in patients with supracondylar humeral fractures. Methods: Data were collected on 210 children with displaced supracondylar humeral fractures. A standardized 15-variable checklist was completed by an orthopaedic resident and attending physician. For each variable, Stuart-Maxwell and McNemar tests were used to determine significant differences ( P <0.05) in marginal frequencies between the two cohorts. Cohen's kappa analysis (κ) quantified agreement between residents' and attending physicians' findings. Κ > 0.75 was considered excellent, 0.40-0.75 moderate, and < 0.40 marginal-poor. Results: The agreement between resident and attending physicians was 89%. Three variables had excellent agreement: hand temperature and color (κ~1), and Gartland fracture type (κ=0.81). Moderate agreement was observed for fracture direction (κ=0.68), pulse (κ=0.52), and radial nerve motor function (κ=0.49). The remaining variables: swelling, ecchymosis, motor function of the median, ulnar, anterior/posterior interosseous, and sensory function of the radial, median, and ulnar nerves had poor-marginal agreement (κ-range:−0.042-0.388). Only the attending physicians noted neurovascular abnormalities in 38/63 documented instances (60%). There was no significant association between agreement and evaluation time intervals or resident experience. Conclusions: Resident physicians and attending physicians agreed in 89% of the documentation; however, disparities were present in nearly 60% of patients with neurovascular abnormalities. Educational initiatives should target improvement of resident performance in upper extremity neurovascular examination in children. With accurate initial assessment, proper care can be provided according to published guidelines.